Geochemical and Geophysical Study in a Degraded Area Used for Disposal of Sludge from a Water Treatment Plant - Ricardo Cosme Arraes Moreira; Geraldo Resende Boaventura; Sandra Alves Nunes; Luciano de Almeida Pinheiro; Carlos Tadeu Carvalho do Nascimento; Davi Rodrigues da Silva; Christiane de Pinna Lira (Applied and Environmental Soil Science)
The effects of disposal of sludge from water treatment plant (WTS) in area damaged by laterite extraction and its consequences to soil and groundwater were investigated. Therefore, the presence and concentration of anthropogenic elements and chemical compounds were determinated. WTS disposal's influence was characterized by electroresistivity method. The WTS's geochemical dispersion was noticed in the first meters of the nonsaturated zone from the lending area. Lateritic profiles were characterized due to the large variation in chemical composition between the horizons. Infiltration and percolation of rainwater through the WTS have caused migration of total dissolved solids to the groundwater. WTS's disposing area has more similarities to local preserved vegetation than to gravel bed area. WTS can be considered a noninert residue if disposed in degraded areas located in regions with similar geological and hydrochemical characteristics.